Critical Analysis of the Political Media Discourse of “Haider Al-Abbadi” the Former Iraqi Prime Minister - Kareem Sherwani, Kawa Abdul; Haseeb Qaradakhy, Bahat (International Journal of Psychosocial Rehabilitation, 2019)
Critical Discourse Analysis is a method recently has been developed to analyze verbal texts especially political discourse. This study uses framework adopted from discourse and manipulation to discover discursive structures within the Iraqi political speeches and find out the ideologies underlying them. The focus of the study is on media political discourse in Iraq, more specifically, televised speeches of the Iraqi Prime Minister Haider Al-Abadi in mid-2017. In the theoretical part of the study, critical discourse analysis, media discourse and political discourse are investigated. In the practical part, the data is analyzed qualitatively. The data consists of 20 political speeches of Haider Al-Abadi televised in 2017. By using the tools of Critical Discourse Analysis, the study tries to analyze these political speeches critically to reveal the hidden agenda and ideology which are concealed from ordinary audience, and to disclose the discourse devices used by Iraqi politicians to gain power and authority. One of the inferences of the study is that Haider Al-Abadi, like many other Arab and Muslim populists, tries to use religious symbols to convince the audience that he is doing right, he has projects to improve the life of Iraqi people, and he is fighting terrorism and corruption.